TINJAUAN YURIDIS TERHADAP SUBJEK HUKUM DALAM TRANSAKSI JUAL BELI ONLINE COMMERCE DITINJAU DARI KITAB UNDANG-UNDANG HUKUM PERDATA - Munte, Herdi; Sinaga, Muhammad Iqbal; Br Sitepu, Tria Feba (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
The practice of online buying and selling in people's lives has not fully run according to the rules in the transactions that have been set, some consumers experience losses because the goods ordered do not match the initial agreement. The government has an important role in the legal validity of online buying and selling transactions in Indonesia. This writing method uses normative juridical. The types of data needed in this study are primary data and secondary data. The results obtained Legal Regulations of Legal Subjects in Online Commerce Transactions Reviewed from Civil Law Article 1320 of the Civil Code meets the requirements for making an agreement because there is a will of both parties stated in the rules and submitting an offer in the thread or online sales stall and Article 1330 of the Civil Code has determined people who are considered capable, if in the future a dispute arises, the legal rules that regulate the minimum age to carry out buying and selling transactions, then the legal force of the agreement